Chemical Constituents of Piper aduncum Linn (Piperaceae) - Ahmad, Fariedah; Rahmani, Mawardi (1992)
The leaves of Piper aduncum were studied for its chemical constituents. The non-polar component has been identified spectroscopically as dillapiole or 1allyl- 4, 5-methylenedioxy-2, 3-dimethoxybenzene while from the polar fraction 2, 6-dihydroxy-4-methoxydihydrochalcone has been isolated